Computer simulations of glycolipid bilayers under anhydrous and hydrated conditions / M.Vijayan Manickam Achari - M.Vijayan , Manickam Achari (2016)
Glycolipids are ubiquitous membrane components and amphiphilic in character. They can be found in a variety of living cells and are involved in cell activities like markers for cellular recognition, cell adhesions, also in signal-receiving and transmitting. Understanding the interplay between the complex cell function to their structural and dynamical properties is important to help design new glycolipid-based materials for many applications in medicine, pharmacy and cosmetics. Molecular dynamics simulation is a useful method to explore the bilayer properties. Using this method we simulated glycolipid bilayers in an anhydrous (dry) and lyotropic (hydrated) conditions. The anhydrous monoalkylated glycolipids (such as bMal-C12, bCel-C12, and bIsoMal-C12) bilayers were compared with a C12C10 branched b-maltoside. It was found that the chain branching in the glycolipid leads to a measurable difference in the dimensions and interactions of the lamellar assembly, as well as more fluid-like behavior in the hydrophobic chain region. Substitution of the maltosyl headgroup of bMal-C12 by an isomaltosyl moiety leads to a significant decrease in the bilayer spacing as well as a markedly altered pattern of inter-headgroup hydrogen bonding. Additionally, the monoalkylated glycosides possess a small amount of gauche conformers (_20%) in the hydrophobic region of the lamellar crystal (LC) phase. In contrast, the branched chain glycolipid in the fluid La phase has a high gauche population of up to _40%. Meanwhile, the rotational diffusion analysis reveals that the carbons closest to the headgroup have the highest correlation times where the rotational dynamics of an isomaltose was found to be 11–15% higher and more restrained near the sugar compared to the other monoalkylated lipids, possibly due to the chain disorder and partial inter-digitation. We have also simulated hydrated bilayers of single and Guerbet branched chain maltosides namely bMal-C12(12%wat), bMal-C12(23%wat), bMal-C12C8(R)(25%wat), bMal-C12C8(S)(25%wat), and bMal-C12C8(RS)(25%wat), in a liquid crystalline La phase. In the hydrated condition, these showed that the increase in hydration level correspondingly increases the area per lipid. The bimodal distribution of angle between the chains and the sugar headgroup with z-axis for bMal-C12(23%wat) showed that the chain and the non-reducing sugar ring may flip and protrude into the headgroup region where these observations suggest the bMal-C12(23%wat) system may begin to shift into a metastable phase where, the lipids may try to reorient themselves into different assembly structure such as the hexagonal phase. We have also found that the intermolecular hydrogen bonding of the sugar rings in maltose headgroup shows no significant change although the bilayers are under the effect of water concentration and temperature difference. We also noticed that the non-reducing sugars from all bilayer systems rotate faster than the reducing sugar. Meanwhile, the exocyclic groups rotate much quicker than the sugar ring itself and there is no chirality effect to the rotational diffusion. The order parameter of chain segments shows that they are quite sensitive to the temperature and water concentration and there is a subtle effect of chirality, especially in the racemic mixture of bilayer. These insights into structure-property relationships from simulation provide an important molecular basis for future design of synthetic glycolipid materials.